Health literacy and health-promoting behaviors among adults at risk for diabetes in a remote Filipino community - Christian Sandor B. Ydirin (Belitung Nursing Journal, 2021)
Background: Diabetes risk assessment is an essential preboarding tool before implementing health literacy programs to change an adult’s health behavior positively. Research has shown an association between health literacy and health behaviors, but there is a dearth of literature that delineates the difference between the health literacy and health behaviors of adults according to their diabetes risks; high risk vs. low risk.Objective: This study aimed to determine the difference between the health literacy and health behaviors of adults and establish the relationship between the two variables when classified according to their diabetes risks.Methods: This study utilized a descriptive cross-sectional design with 400 adults in a remote Filipino community in November 2019. Data were gathered using the Health Promoting Lifestyle Profile II (HPLP II) and Health Literacy Survey-Short Form 12 (HLS-SF12) questionnaires. Descriptive statistics, independent t-test, and Pearson’s r were used to analyze the data.  Results: There is a significant difference between the health literacy index scores (p < .05); but no significant difference between the health behavior mean scores (p > .05) of adults when grouped according to their diabetes risks. Health literacy is significantly (p < .05) correlated with health behaviors of adults, with a moderate positive correlation in the high-risk group (r = .43), and both weak positive correlation in the low-risk group (r = .13) and entire group (r = .17).Conclusion: All adult inclusion efforts in promoting health literacy, with emphasis on the high-risk group, are needed to improve awareness of the degree of diabetes risks. Nurses should take an active role in the assessment of diabetes risks, evaluation of results, and implementation of interventions that could increase health literacy to facilitate the development of healthy behaviors. Stakeholders are urged to advance the availability of evidence-based lifestyle interventions to reduce the growth in new cases of diabetes.